Innovation Performance Measurement in Entrepreneurial Business: A Comparative Study between Start-ups and More Established Enterprises - Mardiani, Eri; Dewi, A.Ratna Sari; Panjaitan, Feliks Anggia Binsar Kristian; Damau, Unika Oktaviani (Westscience Press, 2023)
Innovation performance measurement is an important aspect of understanding and improving entrepreneurial success, which has implications for economic development, organizational growth, and community welfare. This study uses comprehensive bibliometric analysis to systematically review and analyze the literature on innovation performance measurement in entrepreneurial business. The research covers startups and established companies, aiming to uncover key themes, influential works, and an ever-evolving research landscape in this dynamic field. His methodological approach integrates bibliometric analysis and visualization using VOSviewer, which provides a holistic view of the intellectual structure in the domain. Key findings include the identification of thematic groups, influential authors, and important works, which provide valuable insights for academics, practitioners, and policymakers involved in fostering innovation and entrepreneurship.